Trusted Computing Platforms TPM2.0 in Context - Proudler, Graeme; Chen, Liqun; Dalton, Chris (Springer International Publishing : Imprint: Springer, 2014)
In this book the authors first describe the background of trusted platforms and trusted computing, and speculate about the future. They then describe the technical features and architectures of trusted platforms from several different perspectives, finally explaining second-generation TPMs, including a technical description intended to supplement the Trusted Computing Group's TPM2 specifications. The intended audience is IT managers and engineers, and graduate students in information security.